Islamicate societies a case study of Egypt and Muslim India, modernization, colonial rule, and the aftermath - Kassim, Husain, 1939-; ebrary, Inc. (Lanham [Md.] : Lexington Books, 2012)
"The book can be used as a textbook for the courses in the Islamic Studies at the undergraduate and graduate level. The unique feature of this book, unlike other books on the subject, is that it combines and presents a complete picture of the 'Islamicate' nature of the Egyptian and Muslim Indian societies by demonstrating the changes that took place in various aspects under the impact of the West and colonial rule. The book would potentially find currency in Muslim countries, especially in Egypt and the Indo-Pakistan subcontinent"--
Machine generated contents note: Introduction: What this study is about -- Chapter 1: The Historical Landscape of Egypt and Muslim India as Islamic Societies Prior to Colonial Rule -- Chapter 2: Shifting Identities : The 'Islamicate' Societies of Egypt, Muslim India (Pakistan), Muslims in India, and its aftermath -- Chapter 3: Ethnicity and Minorities -- Chapter 4: Transformation of Traditional Islamic Language and Literature into a Modern 'Islamicate' Literature -- Chapter 5: Legal System and Judicial Institutions of Egypt and Muslim India -- Chapter 6: Education, Educational System and Islamization Project of Knowledge -- Chapter 7: An 'Islamicate' Woman: Gender Relations and Women's Rights.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Islam -- Social aspects -- Egypt; Islam -- Social aspects -- India; India -- Social conditions -- 21st century; Egypt -- Social conditions -- 1981-; Electronic books